Evaluate the Role of Ginseng Roots against the Toxic Effect of Ibuprofen on Lipid Profiles, Liver Enzymes and Oxidative Stress Status in Male Albino Rats - Hamad, Shelan Abd UlSalam; Wadee, Siham Agmee; Obaid, Wasan Sarhan (American Journal of Biology and Natural Sciences, 2025)
Introduction & aim: The therapeutic qualities of ginseng (Panax ginseng) have attracted a lot of interest. So, this investigation was aimed to study the effect of alcoholic Ginseng extract against Ibuprofen induced reproductive dysfunction in male rat. Materials & methods: From August 24 to September 26, 2024, this study was carried out in the Veterinary Medicine College's animal house at Tikrit University. From the animal house of the Veterinary Medicine College at Tikrit University, fifty (70) adult, seemingly healthy Albino male rats were acquired. Results: A significant (P≤0.05) differences were found in the concentration of cholesterol, triglyceride, LDL, HDL, where the highest concentration was in the fourth group, which administrated Ibuprofen for 30 days compared to the control group, while the treated groups revealed non-significant (P≤0.05) variations from the untreated group. In the ginseng group, the cholesterol levels revealed significant (P≤0.05) reduced from the untreated group. for Liver enzymes, AST, ALT and ALP activity in Ibuprofen (30 days) group revealed significant (P≤0.05) variations from the untreated group. also, in the treated groups and ginseng group revealed significant (P≤0.05) variations from the untreated group. for oxidative stress, MDA levels in Ibuprofen (30 days) group revealed significant (P≤0.05) variations from the untreated group. while, in the treated groups and ginseng group showed significant (P≤0.05) reduced compared to the control group. The SOD levels in Ibuprofen (30 days) group showed non- significant (P≤0.05) differences compared to the control group. also, in the treated groups and ginseng group showed non-significant (P≤0.05) differences compared to the control group. Conclusions: Its concluded that the alcoholic extract of ginseng roots shows a protective and therapeutic effect liver enzymes and its act as antioxidant regents.